STANDARISASI BIMBINGAN KONSELING PADA SEKOLAH (STUDI ANALISIS DI MTS NURUL HUDA) - Andriyani, Wiwik Dyah; Nurzaman, Cepi; Nurfarid, Cucu; Sapulloh, Asep (Penerbit Widina, Widina Media Utama, 2022)
This research aims to answer the following questions: 1) What is the definition of school counseling? 2) What is the right standard of counseling guidance to be applied in schools? The writing objectives are as follows: 1) To find out the purpose or definition of counseling guidance in schools. 2) To know the right counseling guidance standards to be applied in schools. The method in this research uses a qualitative approach. The results showed that there are four important elements for the creation of counseling guidance in accordance with the standards, especially in the school environment. (1) The right counseling teacher, (2) The appropriate program (3) Adequate space (4) Support from the school and other teachers. The right counseling guidance teacher is one who understands the code of ethics of counseling guidance, has the competence to be a counseling guidance teacher and understands his/her duties. Support from the school and other teachers is the participation of the school as well as other teachers to create successful counseling guidance.ABSTRAKPenelitian ini bertujuan untuk menjawab beberapa pertanyaan sebagai berikut: 1) Apa yang di maksud/depinisi bimbingan konseling pada sekolah? 2) Bagaimana standar bimbingan konseling yang tepat untuk di terapkan pada sekolah? Adapun tujuan penulisannya adalah sebagai berikut: 1) Untuk mengetahui maksud atau depinisi dari bimbingan konseling pada sekolah. 2) Untuk menegtahui standar bimbingan konseling yang tepat untuk di terapkan pada sekolah. Metode dalam penelitian ini menggunakan pendekatan kualitatif. Hasil penelitian menunjukan bahwa Ada empat elemen penting demi terciptanya bimbingan konseling yang sesuai dengan standar terutama di lingkungan sekolah. (1) Guru bimbingan konseling yang tepat, (2) Program yang sesuai (3) Ruangan yang memadai (4) Dukungan dari sekolah dan guru-guru lainnya. Guru bimbingan konseling yang tepat ialah yang memahami kode etik bimbingan konseling, memiliki kompetensi menjadi guru bimbingan konseling dan memahami tugas yang dipikulnya. Dukungan dari sekolah dan guru-guru lainnya adalah turut sertanya sekolah juga guru lain demi menciptakan bimbingan konseling yang sukses.